Income Distribution and the Business Cycle - Shahee, Mostafa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
This thesis consists of six chapters. The first chapter is devoted to the introduction to explore how the income distribution within the countries has become a prominent issue in policy making over time. In the second chapter, the related literature on income distribution, GDP and the relationship between these two variables is reviewed. The methodology used for dating the business cycles is extensively explained in the third chapter. The remaining chapters constitute three self-contained essays. The investigation of a possible relationship between the degree of income equality within the countries, and the severity of recession and expansion phase of business cycles, is examined using two different methods. To carry out the investigation reported in chapters four, five and six we use data collected for 40 years on Gini index values and the GDPs of 36 selected countries. The main goal in the first essay is to determine how the deepness and duration of cycles of GDP is correlated with the Gini index values of countries and whether this relationship is mainly sourced from consumption or investment. Likewise, an investigation is carried out to determine if the number of cycles in consumption, investment and GDP of countries could be associated with the level of income inequality in those countries. The results of the correlation and the t-test analysis indicates that income inequality leads to a deeper and longer decline of GDP, which causes a greater cumulative income loss of GDP during a recession period, and a somewhat faster speed of recovery during an expansion period. In addition, the result of a correlation between Gini index values and the number of cycles in consumption, investment and GDP indicate that income inequality is associated with a greater number of cycles in consumption and GDP and a lower number of cycles in investment. In the second essay, the relationship between income equality and the recession is theoretically examined. Models are presented to show how the movement of four components of GDP as consumption, investment, government spending and net export takes place during a recession period for the countries with different level of income distribution. This shows that the countries with a more equality of income distribution would experience a less costly recession. For empirical analysis the instrumental variable is employed in which the findings of empirical analysis support the theoretical arguments. In the third essay, an instrumental variable analysis is employed to find a possible relationship between income inequality and the intensity of expansionary phase of cycles. Although the signs of the coefficients indicate that a more equal income distribution is associated with a somewhat faster recovery, the results are not statistically significant. Keywords: Income Distribution, Business Cycle, Recession, Expansion, Instrumental Variable, Cumulative Loss and Amplitude

Öz: Bu tez altı üniteden oluşmaktadır. Ülkeler içinde gelir dağılımının zamanla politika geliştirmede nasıl öne çıkan bir mesele olduğunu araştırmak için birinci bölüm girişe ayrılmıştır. İrdelenecek problemi tanımlamak ve analizimize sağlam bir temel oluşturmak için ikinci bölümde gelir dağılımı, gayri safi yurtiçi hasıla (GSYİH) ve bu iki değişken arası ilişki üzerine ilgili literatür (alanyazın) taranmıştır. Üçüncü bölümde iktisadi dalgalanmaları belirlemek için kullanılan metodoloji kapsamlı bir şekilde açıklanmıştır. Geri kalan dört, beş ve altıncı bölümler bağımsız üç makaleden oluşmaktadır. İki farklı yöntem kullanarak bir yanda ülkeler içinde gelir eşitliği diğer yanda iktisadi dalgalanmaların resesyon (durgunluk) ve büyüme safhalarının şiddeti arasındaki olası ilişki incelenmiştir. Bölüm dört, beş ve altıda açıklanan incelemeyi yürütmek için seçilmiş 36 ülkenin Gini katsayıları ve GSYİH‟ları üzerine toplanan 40 yıllık veri kullanılmıştır. Birinci makalede esas amaç GSYİH dalgalanmalarının derinliği ve süresinin ülkelerin Gini katsayıları ile nasıl ilişkili olduğunu ve bu ilişkinin esas olarak tüketimden ya da yatırımdan kaynaklandığını belirlemektir. Aynı şekilde, ülkelerin tüketim, yatırım ve GSYİH‟larındaki dalgalanma sayısının bu ülkelerdeki gelir eşitsizliği düzeyi ile bağlantılı olup olmadığını belirlemek için bir araştırma yürütülmüştür. Korelasyon ve t-testi analiz sonuçları göstermektedir ki gelir eşitsizliği GSYİH‟nın daha derin ve uzun süreliğine düşmesine neden olmaktadır, ki bu da GSYİH‟da daha büyük bir resesyon süresince kümülatif gelir kaybına (CTS), ve kısmen daha yüksek bir büyüme süresince iyileşme hızına (ETS) sebep olmaktadır. Ek olarak, Gini katsayıları ve tüketim, yatırım ve GSYİH dalgalanma sayısı arasındaki bir ilişki sonucu göstermektedir ki gelir eşitsizliği tüketim ve GSYİH‟da daha büyük bir dalgalanma sayısı ve yatırımda daha düşük bir dalgalanma sayısı ile ilişkilidir. İkinci makalede gelir eşitsizliği ile resesyon arasındaki ilişki teorik olarak incelenmiştir. GSYİH‟nın dört unsuru olan tüketim, yatırım, devlet harcamaları ve net ihracat hareketinin farklı gelir dağılımı olan ülkelerde resesyon süresince nasıl yer aldığını gösteren modeller sunulmuştur. Bu göstermektedir ki gelir dağılımının daha eşit olduğu ülkeler daha düşük maliyetli bir resesyon yaşayacaklardır. Bir enstrümantal değişken analizi yapılmıştır. Ampirik analiz sonuçları teorik tartışmalarla gelir eşitsizliği ve resesyon şiddeti arasındaki ilişkiyi konu alan birinci makalenin sonuçlarını desteklemektedir. Son olarak, üçüncü makalede gelir eşitsizliği ve genişlemeci dalgalanma safhasının yoğunluğu arasındaki olası bir ilişkiyi bulmak için bir enstrümantal değişken analizi kullanılmıştır. Katsayıların işaretleri daha eşit bir gelir dağılımının kısmen daha hızlı bir iyileşme ile ilişkili olduğunu göstermesine rağmen, sonuçlar istatistiksel olarak anlamlı değildir
Doctor of Philosophy in Economics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2014. Supervisor: Prof. Dr. Mehmet Balcılar.
Keywords: Economics; Income distribution; Business Cycle; Recession; Expansion; Instrumental Variable; Cumulative Loss and Amplitude